UPAYA GURU DALAM MENINGKATKAN KEMAMPUAN BAHASA ANAK MELALUI METODE TANYA JAWAB MENGGUNAKAN MEDIA KARTU BERGAMBAR PADA KELOMPOK A PAUD YRAS MANDIRI KECAMATAN ULU BELU KABUPATEN TANGGAMUS - Meylanieka Wulandari; M Feri Fernadi; Reni Dwi Puspita (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2025)
This research focuses on the problem of how teachers make efforts to improve children’s language skills through the question and answer method using picture cards for group A children as well as what are the supporting and inhibiting factors in improving the language skills of group A children, which aims to find out how teachers make efforts to improve their abilities. language in children through the question and answer method using picture cards for group A children and to find out what are the supporting and inhibiting factors in improving the language skills of group A children.This research uses descriptive qualitative methods. This research was carried out at PAUD Yras Mandiri, Ulu Belu District, Tanggamus Regency, academic year 2022/2023 and carried out from January 2023 to April 2023. This research involved 20 students in class A, data collection techniques namely observation, structured interviews, and documentation. The results of this research show that the teacher’s efforts to improve children’s language skills through the question-and-answer method using picture card media in group A PAUD Yras Mandiri, Ulu Belu District, Tanggamus Regency show that the results obtained state that 0 students are in the Not Yet Developed category, 4 students are in the Starting to Develop category, 11 students are in the Developing According to Expectations category, 5 students are Developing Very Well. The Developing According to Expectations category is quite large, namely 11 students. This means that efforts to improve children’s language skills through the question and answer method using picture cards are said to be successful. This research focuses on the problem of how teachers make efforts to improve children’s language skills through the question